2012
DOI: 10.1371/journal.pone.0047969
|View full text |Cite
|
Sign up to set email alerts
|

Towards National Surgical Surveillance in the UK – A Pilot Study

Abstract: ObjectiveThe Bristol heart inquiry in the United Kingdom (UK) highlighted the lack of standards for evaluating surgical performance and quality. In 2009, the World Health Organisation (WHO) proposed six standardised metrics for surgical surveillance. This is the first study to collect and analyse such metrics from a cohort of National Health Service (NHS) Trusts in England, helping to determine their feasibility and utility in measuring surgical performance, its impact on public health and mortality, and for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previously, obtaining such information apart from official reports and documents was challenging. One of the included articles attempted to obtain data by a simple letter, and achieved a response rate of 11%; this improved to 83% after making the FOI Act request 19. A similar act passed in the USA in 1966 led to a vast public health and medical research output 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, obtaining such information apart from official reports and documents was challenging. One of the included articles attempted to obtain data by a simple letter, and achieved a response rate of 11%; this improved to 83% after making the FOI Act request 19. A similar act passed in the USA in 1966 led to a vast public health and medical research output 25.…”
Section: Discussionmentioning
confidence: 99%
“…One of the included articles attempted to obtain data by a simple letter, and achieved a response rate of 11%; this improved to 83% after making the FOI Act request. 19 A similar act passed in the USA in 1966 led to a vast public health and medical research output. 25 The FOI Act in the UK now enables researchers to access a similarly large amounts of data pertaining to the entirety of the health service at minimal expense—both financially and with respect to time for researchers.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have suggested that compliance in completing the checklist is minimal [8] , [9] . Monitoring the implementation and compliance with safety and quality assurance systems is an important aspect of clinical audit and surgical surveillance [10] . Data on WHO checklist compliance for a subset of our patients was lacking locally.…”
Section: Introductionmentioning
confidence: 99%